2007
DOI: 10.1088/0953-2048/20/8/013
|View full text |Cite
|
Sign up to set email alerts
|

Measuring transport AC losses in YBCO-coated conductor coils

Abstract: Several AC power applications of YBCO-coated conductors (CCs) involve superconducting tapes wound in coils. In such a configuration the superconducting tape is arranged as closely packed turns, which strongly interact due to the generated magnetic field. This has a strong influence on the AC losses, which are different from those of an isolated tape, and need to be precisely quantified in order to predict and reduce the refrigeration requirements of applications. In this paper we experimentally evaluate the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 12 publications
6
77
0
Order By: Relevance
“…Conducted investigations showed that the return of a winding into the superconducting state after short circuit clearing depends primarily on the ratio between the short circuit current and the rated load current [9][10][11][12][13][14]. In other words, the ratio between the short circuit current and the load current should be a such value that the quantity of heat does not exceed the critical value during a short circuit.…”
Section: Q I T W T T T T T T Ctmentioning
confidence: 99%
“…Conducted investigations showed that the return of a winding into the superconducting state after short circuit clearing depends primarily on the ratio between the short circuit current and the rated load current [9][10][11][12][13][14]. In other words, the ratio between the short circuit current and the load current should be a such value that the quantity of heat does not exceed the critical value during a short circuit.…”
Section: Q I T W T T T T T T Ctmentioning
confidence: 99%
“…Therefore, an approximate 2D axisymmetric model is built for the joint-free coil. The model is based on H-formulation of HTS, whose governing equation is as: [31][32][33][34][35][36][37][38] …”
Section: B Numerical Modelmentioning
confidence: 99%
“…Ultimately, assess the possibility of applying the superconducting material on electromagnetic levitation. So the primary issue of applying high-temperature superconducting material in maglev system is to study the magnitude of AC loss [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%